Employee Involvement in Internal Communication Activities PT. Pertamina Hulu Energi - Anggadewi Widyastuti; Ayu Christy; Ratih Sekar Pratiwi; Namira Rahajeng Permatatika (Ikatan Sarjana Komunikasi Indonesia, 2024)
Employee involvement is important for a company, where it shows how responsive employees are to the programs created by the company for its employees. How responsive employees are to an activity held by the company's internal communications is also a good record for the internal communications department. This research aims to examine employee involvement at PT. Pertamina Hulu Energiin programs held by the company's internal communications. The research was conducted using descriptive quantitative methods by distributing questionnaires to 470 employees spread throughout Indonesia and also from international branches. The research results show that employee involvement in activities held by the internal organization is very necessary to measure the efficiency and effectiveness of these activities. Communication channels also play a role in the effectiveness of delivering messages to reach employees. How to ensure that messages are well received by employees also requires a good strategy. By integrating internal communications strategies with employee engagement factors such as a participative culture, a supportive communications climate, and the quality of information flow, organizations can build a solid framework that strengthens consistency and synergy between internal communications and employee engagement.